Reflective Practice in Pre-Service Educational Leaders: An Analysis of Video-Based Learning and Peer Feedback (Journal of Advanced Research in Social Sciences, 2025)
Providing opportunities for future school leaders to reflect and assess their communicative skills, their data leadership, and their ability to adjust and grow is critical to the development of strong school leaders. While the need for reflection is often linked to excellence in teaching (Schon, 1983), the building of professional competence and excellence in related educational roles, such as leadership, can also be linked to reflective practices. In recognition of the landscape of diverse schools and communities across the United States, cultivating leaders who stand ready to serve as reflective practitioners may be more critical now than ever before (Roberts, 2008). In addition, online programs, while often criticized for a lack of opportunity to practice speaking skills, stand in a good position to lead the integration of needed skills into reflective experiences. This study focused on such an opportunity within an entirely asynchronous online leadership program, and explored student perceptions on the impact of their leadership growth and the potential of reflective practice while using video capture and peer feedback.